(untitled) (Canadian Eye Care Today, 2024)
Microbial keratitis is a vision-threatening infection of the cornea and an important cause of ocular morbidity that can result in blindness. It is estimated that over 1.5 million people worldwide will develop blindness from infectious corneal ulceration each year. If left untreated or treated incorrectly, it can result in progressive tissue destruction with corneal perforation or extension of the infection to the adjacent tissue. Outcomes of these patients depend on timely diagnosis and treatment with close follow-up.